Students' mathematical critical thinking ability in problem-based learning viewed based on learning style - Bambang Eko Susilo (Universitas Hamzanwadi, 2022)
The development of mathematical critical thinking ability and individual uniqueness in the learning of prospective teacher students needs attention so that they have sufficient provisions in their future work. This study aims to analyze the differences in prospective teacher students' mathematical critical thinking ability in their achievement and improvement from two different learning models and their learning styles. Problem-based learning was used in the experimental group, while the control group used conventional learning. This study used a quasi-experimental quantitative method with the pretest-posttest non-equivalent group design. Data were collected using: mathematical critical thinking ability test and a learning style questionnaire. Data were taken from 56 students of the Mathematics Education Study Program, Universitas Negeri Semarang. Data analysis was performed using independent samples t-test, Mann-Whitney U test, and normalized gain. The results showed that in the achievement and improvement of mathematical critical thinking ability, students who obtained Problem-based learning overall and viewed from a kinesthetic learning style were better than conventional learning. Meanwhile, in terms of auditory and kinesthetic learning styles, the mathematical critical thinking ability of students who obtained descriptive problem-based learning was better. However, in statistical testing, the two groups were not significantly different. Based on these results, Problem-based learning is considered adequate for developing mathematical critical thinking ability, especially for kinesthetic learning styles.